2014
DOI: 10.5665/sleep.3662
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Sleep Apnea Resolution Study: A Prospective Randomized Controlled Trial of Continuous Positive Airway Pressure Versus Adaptive Servoventilation Therapy

Abstract: Clinicaltrials.Gov NCT00915499.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 36 publications
2
58
0
2
Order By: Relevance
“…Some authors have suggested that a poor initial experience with PAP therapy due to residual disease may lead to long-term nonadherence with PAP in some patients (19,20,23). Such a finding would theoretically support the concept of early intervention (perhaps with a newer ASV device) in such patients to avoid long-term nonadherence.…”
Section: Respondersmentioning
confidence: 72%
See 2 more Smart Citations
“…Some authors have suggested that a poor initial experience with PAP therapy due to residual disease may lead to long-term nonadherence with PAP in some patients (19,20,23). Such a finding would theoretically support the concept of early intervention (perhaps with a newer ASV device) in such patients to avoid long-term nonadherence.…”
Section: Respondersmentioning
confidence: 72%
“…Such a finding would theoretically support the concept of early intervention (perhaps with a newer ASV device) in such patients to avoid long-term nonadherence. This concept is currently being studied (19), but our data do not support the use of ASV in an early intervention strategy for the purposes of improving adherence. Whether there are implications for sleep apnea symptoms and cardiovascular outcomes remains to be fully determined.…”
Section: Respondersmentioning
confidence: 94%
See 1 more Smart Citation
“…However, these findings make part of the ongoing debate about CompSA being solely treatment-emergent or transient CA, which could in many cases resolve spontaneously over time (10,21). In a very recent prospective randomized trial (CPAP vs adaptive servo-ventilation device (ASV)), Morgenthaler and colleagues (24) showed in an intention-to-treat analysis that, after 90 days of therapy, significantly more CompSA patients improved under ASV (89.7%) than under CPAP (64.5%). Whether pre-existing supposed chemo-reflex dysfunction can positively evolve in any patient is therefore questionable.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, it does raise the possibility that it might be responsible for CPAP discontinuation in some patients and therefore treatment might be helpful in patients with persistent or late emergence of CPAP emergent CSA. In this regard ASV is superior to other modalities for treatment of CPAP emergent CSA (11).…”
mentioning
confidence: 96%